Del “instante” y la categoría de lo posible/On the “instant” and thecategory of possibility - Marianella Lorenzo (ETD: Educação Temática Digital, 2010)
El objeto de este escrito es mostrar posibles articulaciones entre la categoría del instante (Kierkegaard) y algunos aspectos de la teoría de Lacan. Mi reflexión se centrará, principalmente, en los conceptos de “instante”, “angustia” y “mirada”. La problemática general involucrada en esta investigación es sólo parcialmente explorada. The aim of this paper is to show possible articulations between the category of the instant (Kierkegaard) and some aspects of the Lacan´s theory. I center most of my reflection on the concepts of “instant”, “anguish” and “sight”. The general problem is only partially explored here.